Meiosis Progression and Recombination in Holocentric Plants: What Is Known? - Hofstatter, Paulo G.; Thangavel, Gokilavani; Castellani, Marco; Marques, André (Frontiers in Plant Science, 2021)
Differently from the common monocentric organization of eukaryotic chromosomes, the so-called holocentric chromosomes present many centromeric regions along their length. This chromosomal organization can be found in animal and plant lineages, whose distribution suggests that it has evolved independently several times. Holocentric chromosomes present an advantage: even broken chromosome parts can be correctly segregated upon cell division. However, the evolution of holocentricity brought about consequences to nuclear processes and several adaptations are necessary to cope with this new organization. Centromeres of monocentric chromosomes are involved in a two-step cohesion release during meiosis. To deal with that holocentric lineages developed different adaptations, like the chromosome remodeling strategy in Caenorhabditis elegans or the inverted meiosis in plants. Furthermore, the frequency of recombination at or around centromeres is normally very low and the presence of centromeric regions throughout the entire length of the chromosomes could potentially pose a problem for recombination in holocentric organisms. However, meiotic recombination happens, with exceptions, in those lineages in spite of their holocentric organization suggesting that the role of centromere as recombination suppressor might be altered in these lineages. Most of the available information about adaptations to meiosis in holocentric organisms is derived from the animal model C. elegans. As holocentricity evolved independently in different lineages, adaptations observed in C. elegans probably do not apply to other lineages and very limited research is available for holocentric plants. Currently, we still lack a holocentric model for plants, but good candidates may be found among Cyperaceae, a large angiosperm family. Besides holocentricity, chiasmatic and achiasmatic inverted meiosis are found in the family. Here, we introduce the main concepts of meiotic constraints and adaptations with special focus in meiosis progression and recombination in holocentric plants. Finally, we present the main challenges and perspectives for future research in the field of chromosome biology and meiosis in holocentric plants.